Ambulatory blood pressure and drug treatment for orthostatic hypotension as predictors of mortality in patients with multiple system atrophy. (27th January 2022) - Pavy‐Le Traon, Anne; Foubert‐Samier, Alexandra; Ory‐Magne, Fabienne; Fabbri, Margherita; Senard, Jean‐Michel; Meissner, Wassilios G.; Rascol, Olivier; Amar, Jacques
Abstract: Objectives: Multiple system atrophy (MSA) is a rare fatal neurodegenerative disease characterized by parkinsonism, cerebellar ataxia and autonomic failure. This study was aimed at investigating possible associations between mortality, 24‐h blood pressure (BP) level and variability, and drug treatments for orthostatic hypotension (OH) in MSA patients. Methods: A total of 129 patients followed at the French Reference Center for MSA who underwent routine 24‐h ambulatory BP monitoring were included. Unified MSA Rating Scale (UMSARS) scores, drug treatments and the occurrence and cause of death were recorded. Results: Seventy patients died during follow‐up (2.9 ± 1.8 years), mainly from terminal illness, pulmonary or sudden death. Multivariate Cox regression analysis, after adjustment for gender, disease duration and severity (UMSARS I+II score), showed that increased daytime systolic BP variability, OH severity and OH drug treatment were independently correlated with mortality. OH treatment was associated with the risk of cardiac causes and/or sudden death ( p = 0.01). In a fully adjusted model, male gender [(female vs. male) hazard ratio (HR) 0.56, 95% CI 0.34–0.94, p = 0.03], UMSARS I+II score (HR 1.04, 95% CI 1.02–1.06, p < 0.01), systolic BP daytime variability (HR 3.66, 95% CI 1.46–9.17, p < 0.01) and OH treatment (HR: 2.13, 95% CI 1.15–3.94, p = 0.02) predicted mortality. Conclusions: Increased daytime BP variability and OH treatment were predictive of mortality in patients with MSA, independently from disease severity. Further studies are required to assess if these associations are explained by more severe autonomic dysfunction or if OH treatment exposes per se to a specific risk in this population. Abstract : We here investigated the prognostic factor of ambulatory blood pressure (BP) and orthostatic hypotension (OH) treatment on mortality in a cohort of 129 multiple system atrophy (MSA) patients. The main findings were independent associations between male gender, disease severity (UMSARS), daytime BP variability and OH treatment with mortality in MSA patients.